Conserved Molecular Mechanism of TyrA Dehydrogenase Substrate Specificity Underlying Alternative Tyrosine Biosynthetic Pathways in Plants and Microbes - Schenck, Craig A.; Men, Yusen; Maeda, Hiroshi A. (Frontiers in Molecular Biosciences, 2017)
L-Tyrosine (Tyr) is an aromatic amino acid synthesized de novo in plants and microbes. In animals, Tyr must be obtained through their diet or synthesized from L-phenylalanine. In addition to protein synthesis, Tyr serves as the precursor of neurotransmitters (e.g. dopamine and epinephrine) in animals and of numerous plant natural products, which serve essential functions in both plants and humans (e.g. vitamin E and morphine). Tyr is synthesized via two alternative routes mediated by a TyrA family enzyme, prephenate or arogenate dehydrogenase (PDH/TyrAp or ADH/TyrAa), typically found in microbes and plants, respectively. Although ADH activity is also found in some bacteria, the origin of arogenate-specific TyrAa enzymes is unknown. We recently identified an acidic Asp222 residue that confers ADH activity in plant TyrAs. In this study, structure-guided phylogenetic analyses identified bacterial homologs, closely-related to plant TyrAs, that also have an acidic 222 residue and ADH activity. A more distant archaeon TyrA that preferred PDH activity had a non-acidic Gln, whose substitution to Glu introduced ADH activity. Thus, the conserved molecular mechanism was involved in the evolution of arogenate-specific TyrAa in both plants and microbes.